2019
DOI: 10.1186/s41983-019-0065-z
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric and sleep abnormalities in school-age children with migraine

Abstract: Background: Migraine is a primary headache that commonly starts in childhood and adolescent's periods with great negative impacts on the educational and psychosocial performances of its sufferers. The objectives of this work were to study the existence and types of sleep and psychiatric abnormalities in school-age children with migraine (SCM). Methods: The study was conducted on 40 SCM and 20 age-and sex-matched healthy control subjects (HCS) submitted to history taking, neurological examination, Pediatric Mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…El-Heneedy and colleagues [ 34 ] showed that increased anxious-depressed symptoms among school children with migraine (SCMs) were positively correlated with disabilities following repeated episodes of migraine [ 34 ]. In parallel, SCMs showed competence and behavioral problems with increased depressive symptoms, social problems, somatic issues, and difficulties with attention.…”
Section: Methods Used To Study Mood In Children With Migrainementioning
confidence: 99%
See 3 more Smart Citations
“…El-Heneedy and colleagues [ 34 ] showed that increased anxious-depressed symptoms among school children with migraine (SCMs) were positively correlated with disabilities following repeated episodes of migraine [ 34 ]. In parallel, SCMs showed competence and behavioral problems with increased depressive symptoms, social problems, somatic issues, and difficulties with attention.…”
Section: Methods Used To Study Mood In Children With Migrainementioning
confidence: 99%
“…In parallel, SCMs showed competence and behavioral problems with increased depressive symptoms, social problems, somatic issues, and difficulties with attention. These consecutively impaired SCMs in their free-time and social activities [ 34 ]. Other studies [ 35 , 36 ] have also found increased anxiety and depression in children with migraine.…”
Section: Methods Used To Study Mood In Children With Migrainementioning
confidence: 99%
See 2 more Smart Citations
“…There were no participants <18 years of age in the PSQI analysis or the MIDAS and PSQI correlational analysis due to a lack of available data. Eleven studies measured PSG in adults [15][16][17][18][19][20] and children [21][22][23][24][25] , with and without migraine. One study 16 compared migraineurs PSG in the pre-, mid-and post-ictal phase, and thus it was not appropriate to extract a single value for this data.…”
Section: Description Of Studiesmentioning
confidence: 99%